Pattern of admission and outcome at a newly established sickle cell center in Nigeria - Ighosewe, Peace A.; Ajaegbu, Obinna C.; Okwudinka, Ifeoma O.; Ezeonwu, Bertilla U.; Ofudu, Prince O.; Mbagwu, Nkemjika E.; Ogbangwo, Helen O.; Enyadike, Agatha U. (International Journal of Contemporary Pediatrics, 2024)
Background: Sickle cell disease (SCD) encompasses a group of autosomal recessive haemoglobinopathies whose genetic mutation leads to the replacement of glutamic acid by valine in position 6 of the beta-globin chain. Most of the world’s SCD burden is in Africa, where it is a major contributor to childhood morbidity and mortality. The study is aimed at determining the pattern of admission and outcome of patients seen at the sickle cell center Asaba, over a two-year period January 2022 to December 2023. Methods: This was a retrospective descriptive study of children with SCD admitted into the sickle cell center of the Asaba specialist hospital. Information obtained included age, gender, diagnosis, month and year of admission, and outcome. Descriptive statistics was used to describe the demographic characteristics and chi-square to assess their association. Results: A total of 338 children were seen, 34.5% of the patients were less than 5 years of age; males were 52.6% while 61.6% of the admission occurred during the rainy season. Vaso-occlusive crisis (80.6%) was the most common crisis seen; malaria (51.9%) was the prominent diagnosis made. Case fatality rate was 1.7%. Conclusions: SCD s remains a major source of admission and mortality in our environment. A comprehensive SCD care plan is needed to reduce the adverse consequences associated with this disease.